The Influence of Training and Supervision of AMC Unit on the Performance of Ground Support Equipment Personnel at Hang Nadim Airport Batam - Chesa Ramadhan, Muhammad; Rhinaldi, Ridho; Budiarto, Anton (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Abstract Training and supervision of the Apron Movement Control (AMC) unit play a crucial role in ensuring smooth and safe airside operations. At Hang Nadim Airport Batam, however, violations and complaints are still observed, indicating that AMC’s training and supervision efforts have not been fully effective. This research analyzes the influence of training and supervision on the performance of Ground Support Equipment (GSE) personnel. The study employed a quantitative method using primary data from questionnaires distributed to 36 respondents, determined with the Slovin formula. Data were analyzed using multiple linear regression. The results show that training contributes 39.2% to performance improvement, while supervision contributes 34.4%. Together, both variables explain 70% of performance variation, with 30% influenced by other factors. The simultaneous F-test results confirm that training and supervision significantly affect GSE performance. This study concludes that AMC’s training and supervision are essential in improving personnel performance at Hang Nadim Airport Batam.